Rick Steves Italy 2025 - Steves, Rick, 1955- (Rick Steves' guidebook series. City, regional and country guides., 2025)
An updated edition of a popular traveler's guide to Italy offers comprehensive recommendations for a multi-week trip, covering everything from major cities and the Forum to the Colosseum and Michelangelo's David while providing walking-tour options and helpful Italian phrases.